Penyuluhan Strategi Keuangan Cerdas untuk UMKM pada Era Digital di Kecamatan Pondok Aren - Ferranti, Putri Andari; Puspitarini, Sari; Hindardjo, Anton (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2024)
In recent years, advancements in digital applications have provided access for all layers of society to easier financial management than traditional methods at their fingertips. However, many small and medium enterprise (SME) operators are still not accustomed or effectively informed about their utilization for their businesses. This outreach aims to help SME operators adapt to the current digital access convenience in managing their business finances. There are various digital applications available that can assist SME operators in addressing issues such as non-positive sales growth, difficulties in accurately tracking operational transactions, or slow traditional funding assistance. This activity introduces ways to easily create financial projections and reports, utilize online financial transaction methods, and explore Fintech alternatives.